Simulation and prediction of geologic hazards and the impacts on homestay buildings in scenery spots through BIM - Zou, Linfeng; Gui, Weimin (PloS one, 2020)
The objectives are exploring the impacts of geologic hazards on the construction of homestays, improving the safety of homestay buildings, guaranteeing the safety of tourists, and enhancing the disaster-resistance of homestays in scenery spots. The computer simulation system and Building Information Modeling (BIM) technology are employed to construct a geologic hazard prediction model for homestays. The model utilizes a time history method to establish a complete early-warning and monitoring system by learning the geologic disaster data. The detection of various geologic hazards has verified the effectiveness of the proposed model. The results show that the model can reduce the losses in the case of water accumulation and landslides during storms, and the BIM technology-based homestay buildings will suffer fewer losses. In the case of earthquakes, BIM technology-based homestay buildings have no noticeable shaking and displacement. Compared to traditional construction methods, the displacement is reduced by 49.15%. In the case of a spontaneous fire, the burning area of the BIM technology-based homestay building is only 270m2. The most severe factors affecting the construction of homestay buildings are earthquakes and landslide risks. The BIM technology generates 3D building planning; therefore, planners can fully understand the problems in the building. In the meantime, the multi-source monitoring data of multiple geologic hazards can be monitored and fed back, thereby improving the timeliness of early-warning of geologic hazards. The results are of considerable significance to the prevention of losses caused by geologic hazards, which can significantly improve the understanding of geologic hazards.